2006
DOI: 10.1007/s00267-005-0294-z
|View full text |Cite
|
Sign up to set email alerts
|

Community Structure and Quality After 10 Years in Two Central Ohio Mitigation Bank Wetlands

Abstract: We evaluate two 10-year-old mitigation bank wetlands in central Ohio, one created and one with restored and enhanced components, by analysis of vegetation characteristics and by comparison of the year-10 vegetation and macroinvertebrate communities with reference wetlands. To assess different measures of wetland development, we compare the prevalence of native hydrophytes with an index of floristic quality and we evaluate the predictability of these parameters in year 10, given 5 years of data. Results show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 39 publications
2
33
1
Order By: Relevance
“…We found differences in the composition of macroinvertebrate assemblages, but in this study the overall level of biodiversity was comparable among the three ecosystem categories. Some authors have found similar taxa richness in natural wetlands and in 1 to 10 year-old constructed wetlands (Barnes, 1983;Stanczak and Keiper, 2004;Hansson et al, 2005;Spieles et al, 2006), but critics often argue that certain aspects of created wetlands (e.g., plant communities and soils) can not be similar to natural wetlands for at least almost 5 years (Campbell et al, 2002). Miguel-Chinchilla et al (2014) have recently demonstrated that environmental factors better explain the pond biodiversity than pond age, influencing the number and type of taxa that are able to colonize man-made ponds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found differences in the composition of macroinvertebrate assemblages, but in this study the overall level of biodiversity was comparable among the three ecosystem categories. Some authors have found similar taxa richness in natural wetlands and in 1 to 10 year-old constructed wetlands (Barnes, 1983;Stanczak and Keiper, 2004;Hansson et al, 2005;Spieles et al, 2006), but critics often argue that certain aspects of created wetlands (e.g., plant communities and soils) can not be similar to natural wetlands for at least almost 5 years (Campbell et al, 2002). Miguel-Chinchilla et al (2014) have recently demonstrated that environmental factors better explain the pond biodiversity than pond age, influencing the number and type of taxa that are able to colonize man-made ponds.…”
Section: Discussionmentioning
confidence: 99%
“…There is also little knowledge on the processes taking place in these artificial environments and on their ecological function, especially at the invertebrate community level (Herrmann et al, 2000;Ruhí et al, 2009). Research on constructed wetlands has most frequently been addressed to evaluate their efficacy in pollution removal and flood mitigation, with less attention to their role as ecosystems (Mitsch et al, 1998;Spieles et al, 2006). Only a few studies (Spieles and Mitsch, 2000;Fairchild et al, 2000;Balcombe et al, 2005;Becerra-Jurado et al, 2009;Gallardo et al, 2012) have analysed the macroinvertebrate communities of constructed wetlands and the environmental factors that influence them.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, mitigation performance criteria are limited to aspects of the plant community composition (Breaux and Serefiddin 1999, Streever 1999, Spieles 2005. While vegetation composition may be a useful indicator of early ecosystem development, many studies have noted that plant community composition metrics fall short of describing the integrity or functionality of the replacement ecosystem (Zedler 2000, Spieles et al 2006. Since mitigation monitoring programs typically assess only the requisite criteria during the mandatory monitoring period, comparatively little is known about the emergent properties of the resulting wetland.…”
Section: Introductionmentioning
confidence: 99%
“…Research on constructed wetlands has most frequently addressed their efficacy in pollutant removal and flood mitigation, with less attention paid to the use of these systems by wetland organisms and functional aspects of the constructed wetland ecosystem (Mitsch et al 1998;Spieles et al 2006). However, small wetlands are important habitat for numerous organisms, both resident (amphibian larvae, invertebrates, vegetation), and transient (adult amphibians and some invertebrates, migratory waterfowl) (Knight 1992;Semlitsch and Bodie 1998;Nelson et al 2000;Houlahan et al 2006).…”
Section: Introductionmentioning
confidence: 98%
“…The potential of SWPs in conservation strategies for wildlife such as amphibians and birds is often emphasized by developers and city planners when proposing new urban development (Mitsch et al 1998;Spieles et al 2006;Schulte-Hostedde et al 2007;Rubec and Hanson 2009). However, while the construction of SWPs may be partly intended to mitigate losses of wetlands that have been damaged or destroyed elsewhere by the development ("no net loss" of habitat), this goal is likely to be in conflict with their primary roles in collection, storage, and/or metabolism of runoff water, sediments, and pollutants (Mitsch 1992;Semlitsch and Bodie 1998;Rubec and Hanson 2009).…”
Section: Introductionmentioning
confidence: 99%